Language preferences of pre-service teachers who specialise in English and an African language - Sigudla, Malefeu Maria; Mabila, Thembinkosi E; Tirivangasi, Happy Mathew (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this article was to provide the language preferences by the pre-service teachers who specialise in English and an African indigenous language for their future employment. The focus was mainly on whether those pre-service teachers would take unsubsidised English and subsidised African indigenous language specialisation. Different studies have investigated the contentious issue of language preference in education, particularly in South Africa. They report that African indigenous languages are insufficiently promoted despite the Constitution’s requirement for equitable treatment of all 11 official languages. The South African Department of Education department intervened to promote the African indigenous languages and to increase the number of teachers for African indigenous languages in schools; through Funza Lushaka Bursary Scheme. Language-in Education Policy (LiEP) was also put in place to promote various languages in unison. The available literature revealed a negative attitude towards the use of African languages. This results in a decline of the African indigenous languages; being unsupported, which poses a challenge particularly in rural areas. A qualitative study was conducted using semi-structured interviews among pre-service language teachers and a purposive sampling was employed. The results showed that most of the participants preferred to teach African indigenous languages (i.e. Sepedi/Xitsonga/TshiVenda) while the rest 30% preferred to teach English. Their preference was founded on a different individual motivation (e.g. culture carrier; language as a legacy; maintain identity; language exploration etc.). It is hoped that the preferred African indigenous languages would enhance the chances that the afore-mentioned languages are supported beyond the schooling period. In conclusion, the study contributed a body of knowledge that the pre-service teachers shown interest in teaching African indigenous languages for their future employment. Further, the researchers can conclude that Funza Lushaka Bursary Scheme is effective in curbing the lack of African indigenous language teachers because those languages were one of the scarce skills subjects in schools. A new body of knowledge was provided by this study that the pre-service teachers demonstrated interest in teaching African indigenous languages for their future employment.There is a need to investigate the sustainment of the African indigenous languages among new teachers in the teaching field.